Assessing Airway Resistance Using Plethysmography as Lung Function Testing Among Asymptomatic Rheumatoid Arthritis Patients.: Life Sciences-Airway resistance indicators for Lung function test of Rheumatid Arthritis - Abdulrhman Mustafa Rasheed; Ahmed Fadlalla; Tarig Fadelelmoula; Alblowi, Wael F; Saitah Fawaz Alshammari; Asmaa Hegazy (International Journal of Life Science and Pharma Research, 2022)
Pulmonary events in rheumatoid arthritis (RA) reflects the involvement of pleurae, lung interstitium, and airways. Overall, pulmonary manifestations are estimated to cause 10–20% of mortalities in RA. Respiratory system involvement as extra-articular presentations of RA is common among some Saudi patients. This study aims to evaluate specific airway conductance (sGaw), airway resistance (Raw), and specific airway resistance (sRaw), using plethysmography. Comparison for deployed methods is made by forced spirometer as an indicator for obstruction among patients with RA. The study sought to use the methods to enhance lung testing among RA patients. An analytical, hospital-based study was carried out at pulmonary function test laboratory, department of respiratory care King Saud Medical City (KSMC). RA patients were selected, with an age group of 18-75years. The tests for Forced spirometer and plethysmography were carried out to assess and analyze how the respiratory mechanism was impacted by the disease. Data collected was analyzed using Statistical Package for Social Sciences (SPSS), version 21. The obstructive and mixed ventilation patterns constituted 15%; the mean values of Raw and sRaw were significantly higher compared to mean values predicted for participants selected during the study, while sGaw was significantly lower compared to mean values predicted for participants selected. Monitoring of airway resistance parameters using plethysmography can be used as indicators of lung function testing among RA patients.